Wind energy potential in the Republic of Maldives - Wahid, Abdulla; Malik, Arif Saeed; Yu, Cun Yi; Heredia, Juan B.; Srivastava, Suresh Chandra; DAAD (Bangkok : Asian Institute of Technology, 1996)
Maldives is a group of small islands situated in the Indian Ocean off the coast of south India. It has few natural resources and has no oil or coal deposits. Imported diesel is used for electricity generation. The resulting high cost of electricity generation has lead to search for alternative sources of energy for electricity generation. This study finds out technical, economic and financial feasibility of wind energy for electricity generation in Maldives. The study is based on the data from two islands. Wind speed of one year (1993) from Male' International Airport and S.Gan were used to assess the wind energy potential in Maldives. The yearly mean wind speed and yearly mean wind power density of Male' is 5.9 mis and 190 W/m2 respectively. The yearly mean wind speed and yearly mean wind power density of S.Gan is 4.0 mis and 74 W/m2 respectively. The Weibull distributions of the wind speed frequencies were derived and compared with the actual data. The Weibull parameters, i.e., shape parameter and scale factor, were calculated graphically and numerically by using Weibull Probability Paper, Standard Deviation Analysis and Energy Pattern Factor method. The shape parameter of Male' and S.Gan was 1.65 and 1.9 respectively. The scale factor of Male' and S.Gan was 4.0 and 6.34 mis respectively. Considering the maximum available wind resource, Male' wind speed data is used for another island, H.A.Dhidhdhoo, whose existing generating capacity and load model was available. A selection of promising wind turbine generators (WT Gs) were then identified and their performances were predicted. Economic and financial electricity generation costs based on diesel generation alone and diesel with wind energy contribution were evaluated. Economic and financial cost of generation with diesel alone was 24 and 37 USc/kWh respectively. Economic and financial cost of generation with diesel and wind, wind penetration at the level of base load, was 27 and 49 USc/kWh respectively. Economic evaluation of water pumping for agricultural use was assessed. Water pumping from diesel-pump and wind-pump was 19 and 69 USc/m3 respectively. This study has shown that at the current level of diesel price and equipment cost, electricity generation from wind is neither economically nor financially attractive compared to the generation from diesel alone. Water pumping by wind pump is also not attractive than that of diesel pump.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1996
Keywords: Wind power -- Maldives